Assessment of the relationship between living alone and the risk of depression based on longitudinal studies: A systematic review and meta-analysis - Wu, Daolin; Liu, Fuwei; Huang, Shan (Frontiers in Psychiatry, 2022)
Background:Living alone is one of the most common psychosocial factors that may have an impact on lifestyle management and health status. Although many previous cross-sectional studies have found that living alone increases the risk of depression. However, this risk has rarely been assessed on the basis of longitudinal studies, and we aimed to explore this relationship from the basis of longitudinal studies. Methods:We systematically searched Pubmed, Embase, and Cochrane databases up to May 2022. Adjusted odds ratios (ORs) , and 95% confidence intervals (CIs) were pooled by a random-effects model using an inverse variance method. Results:Seven studies(six cohort studies and one case-control study) were included in our study. 123,859 without a history of psychosis individuals were included, and the proportion of females was 65.3%. We applied a random-effects model to minimize the heterogeneity. Overall, the pooled data suggests that people living alone are associated with an increased risk of depression compared to those who do not live alone (HR 1.42, 95%CI 1.19 - 1.70). Conclusion:Living alone increases the risk of depression compared to people who live with others. Keywords: Living alone · depression ·longitudinal studies ·systematic review · Meta-analysis